Establishing reference intervals for islet autoantibodies in Han Chinese type 1 diabetes. (1st December 2021) - Fu, Yu; Zhang, Chen; Gu, Yong; Ge, Shibin; Li, Jianhua; Feng, Jianlin; Zhang, Li; Liu, Wei; Chen, Heng
Abstract: Currently, islet autoantibodies (IAbs) constitute the most reliable marker for detecting the autoimmune process of type 1 diabetes (T1D). However, there are no appropriate reference intervals (RIs) to interpret the results of IAbs in China. In this study, we aimed to establish the RIs of four common IAbs based on the Han Chinese population and evaluate their clinical diagnostic values in patients with T1D. We collected 177 blood samples from healthy volunteers to detect the levels of IAbs directed against insulin (IAA), glutamic acid decarboxylase-65 (GADA), insulinoma antigen 2 (IA-2A), and zinc transporter-8 (ZnT8A) using a chemiluminescence immunoassay. RIs were calculated using nonparametric 95th percentile intervals in accordance with the Clinical and Laboratory Standards Institute guidelines, and their clinical diagnostic values were evaluated by detecting the levels of IAbs of 140 blood samples from patients with T1D in a clinical setting. We defined 138 individuals as the apparently healthy population from the 177 healthy volunteers based on the exclusion criteria. No association between the levels of the four IAbs and gender ( p  > .05) and age ( p  > .05) were found in the apparently healthy population. The combined RIs for GADA, IA-2A, ZnT8A, and IAA were 0–1.78 IU/mL, 0–3.91 IU/mL, 0–2.36 AU/mL, and 0–0.58 COI, respectively. Overall, the diagnostic efficiency for the four IAbs, especially for GADA and IAA, were improved by using the RIs established in this study. The RIs for IAbs established in this study will be a valuable tool for disease diagnosis and the therapeutic management of T1D in a clinical setting.